Transition Considerations and Challenges for Transgender Individuals Serving in the United States Military: A Guide for Mental Health Providers. (2nd January 2018) - Love, Heather A.; Mendez, Marcos; Crawford, Caitlyn; Stith, Sandra; LeFeber, Tirzah
ABSTRACT: The United States Secretary of Defense lifted the ban against transgender individuals who meet certain criteria serving openly in the military in June 2016. This shift is accompanied by policy changes, directives, and additional information that can be difficult for mental health providers to navigate. The purpose of this article is to enhance mental health providers' understanding about common challenges for the transgender community and specific military regulations regarding transgender individuals. Furthermore, in this article we seek to provide clinical guidance on working with this unique population.